2014
DOI: 10.1111/codi.12779
|View full text |Cite
|
Sign up to set email alerts
|

Doppler‐guided transanal haemorrhoidal dearterialization for haemorrhoids: results from a multicentre trial

Abstract: Aim This multicentre study, based on the largest patient population ever published, aims to evaluate the efficacy of Doppler-guided transanal haemorrhoidal dearterialization (THD Doppler) in the treatment of symptomatic haemorrhoids and to identify the factors predicting failure for an effective mid-term outcome.Method Eight hundred and three patients affected by Grade II (137, 17.1%), III (548, 68.2%) and IV (118, 14.7%) symptomatic haemorrhoidal disease underwent THD Doppler, with a rectal mucopexy in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…This is same with the results obtained by the above studies. This study revealed no difference between the two groups with respect to postoperative complications and recurrent prolapse after 1 year; The same results were obtained by different studies such as Ratto C et al 17 . Also this study revealed disturbance of the ano-rectal function in the form of urgency, tenesmus, flatus incontinence, more in the hemorrhoidectomy group B but it was not statistically significant, and these symptoms were disappeared after one month from surgery, this result is same as study done by Elshazly WG 18 .…”
Section: Discussionsupporting
confidence: 89%
“…This is same with the results obtained by the above studies. This study revealed no difference between the two groups with respect to postoperative complications and recurrent prolapse after 1 year; The same results were obtained by different studies such as Ratto C et al 17 . Also this study revealed disturbance of the ano-rectal function in the form of urgency, tenesmus, flatus incontinence, more in the hemorrhoidectomy group B but it was not statistically significant, and these symptoms were disappeared after one month from surgery, this result is same as study done by Elshazly WG 18 .…”
Section: Discussionsupporting
confidence: 89%
“…THD or DGHAL is a treatment option for II-and IIIdegree haemorrhoids and in experienced hands possibly also for IV degree [18,108,109]…”
Section: Transanal Hemorrhoidal Dearterialization (Thd) or Doppler-gumentioning
confidence: 99%
“…New studies about physiology published by Morinaga in 1995, at the beginning ignored by great part of surgical community, but with the merit of switching attention form the technical approach to the physiological cause of hemorrhoidal disease and its evolution: vascularization. After more or less 10 years and the development of surgical devices that are dedicated to operate with a standard technique, the Transanal Hemorrhoidal Desarterialization stepped up as a new and minimally invasive approach for the treatment of hemorroids [20][21][22][23][24][25][26][27][28].…”
mentioning
confidence: 99%